Viable Sweetpotato Technologies in Africa (VISTA) Mozambique project - Zano, F. (International Potato Center, 2015)
The Viable Sweetpotato Technology in Africa (VISTA) is a three-year project which began in October 2014 and aims to contribute to improved nutrition, food security and incomes among smallholder farming families through increased production and better utilization of nutritious OFSP varieties, especially by those most at risk of VAD: children under the age of five and pregnant and lactating women. This flyer is a brief of the work being done in four districts in Nampula Province (Monapo, Meconta, Rapale and Murrupula) and two in Zambezia Province (Alto Molócuè and Gurúè).